Use of Adobe Flash Media in Direct Learning to Improve Students' English Vocabulary Mastery X IPA SMAN 12 Berau - Ahmad Bahruddin Ahmad Bahruddin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
The process and the result of English study, especially the mastery of vocabulary among the first grader's students of science class year 2020-2021, are still unsatisfied yet (low). The standard vocabulary mastery can also cause the soft skill in other language aspects, namely reading, listening, writing, and speaking.This action research aims to know the effect of using interactive media using Adobe Flash implemented indirect instruction conducted virtually on Zoom, the material taught was vocabulary. It is used Kemmis and Taggart's model containing two cycles. The technique of gathering data using the test is implemented on both two processes. The method of analyzing data using comparative analysis to gain each score average each cycle. The result shows that the scoring average in cycle 2 is higher, 88,83 (83%), than in cycle 1, 75,9 (52%).The conclusion of this action research shows that the use of interactive multimedia using Adobe Flas implemented indirect instructions can increase the vocabulary mastery among first grader students of the science department at SMAN 12 Berau in the academic year 2020-2021